DEMAND ESTIMATION FOR INDONESIAâS RATTAN IN GERMANY : A Transcendental Logarithmic Function Analysis - , Nofi Sugiyanto, Ching_Yang Lin, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study examines the demand for Indonesiaâs rattan in Germany from 1991-2008 by using Transcendental Logarithmic as a tool. Germany is chosen since it is the potential market of rattan, especially in Europe and it can be considered as a competitive market. The results revealed that the nominal expenditure affects negatively to share of Chinaâs rattan demand, while the others are influenced positively. In term of own-price, Chinaâs, Singaporeâs and Indonesiaâs rattan are inelastic goods in which Indonesiaâs rattan has the lowest value or close to zero. It implies that Indonesiaâs rattan close to perfectly inelastic, while cross price elasticity shows that Malaysiaâs rattan is complement goods of Indonesiaâs rattan. Based on our policy analysis, the export of rattan raw materials is still giving economic profit for Indonesia.